Poor nutritional status but not cognitive or functional impairment per se independently predict 1 year mortality in elderly patients with hip-fracture. Issue 4 (August 2019) - Zanetti, Michela; Gortan Cappellari, Gianluca; Ratti, Chiara; Ceschia, Giuliano; Murena, Luigi; De Colle, Paolo; Barazzoni, Rocco
Summary: Background & aims: Hip fractures are strongly associated with mortality in the elderly. Studies investigating predisposing factors have suggested a negative impact of poor nutritional, cognitive and functional status on patient survival, however their independent prognostic impact as well as their interactions remain undefined. This study aimed to determine whether poor nutritional status independently predicts 1 year post-fracture mortality after adjusting for cognitive and functional status and for other clinically relevant covariates. Methods: 1211 surgically treated hip fracture elderly (age ≥ 65) patients consecutively admitted to the Orthopaedic Surgery Unit of the "Azienda Sanitaria Universitaria Integrata Trieste" (ASUITs), Cattinara Hospital, Trieste, Italy and managed by a dedicated orthogeriatric team. Pre-admission nutritional status was evaluated by Mini Nutritional Assessment (MNA) questionnaire, cognitive status by Short Portable Mental Status Questionnaire (SPMSQ) and functional status by Activity of Daily Living (ADL) questionnaire. All other clinical data, including comorbidities, type of surgery, post-operative complications (delirium, deep vein thrombosis, cardiovascular complications, infections, need for blood transfusions) were obtained by hospital clinical records and by mortality registry. Results: Poor nutritional status (defined as MNA ≤23.5), increased cognitive and functional impairment were all associated with 3-, 6- and 12 month mortality (p < 0.001). Both cognitive and functional impairment were associated with poor nutritional status (p < 0.001). Logistic regression analysis demonstrated that the association between nutritional status and 3-, 6- and 12- month mortality was independent of age, gender, comorbidities, type of surgery and post-operative complications as well as of cognitive and functional impairment (p < 0.001). In contrast, the associations between mortality and cognitive and functional impairment were independent (p < 0.001) of demographic (age, gender) and clinical covariates but not of malnutrition. Kaplan-Meier analysis showed a lower mean survival time (p < 0.001) in patients with poor nutritional status compared with those well-nourished. Conclusions: In hip fracture elderly patients, poor nutritional status strongly predicts 1 year mortality, independently of demographic, functional, cognitive and clinical risk factors. The negative prognostic impact of functional and cognitive impairment on mortality is mediated by their association with poor nutritional status.